2015
DOI: 10.1016/j.jhydrol.2015.07.049
|View full text |Cite
|
Sign up to set email alerts
|

What have we learned from deterministic geostatistics at highly resolved field sites, as relevant to mass transport processes in sedimentary aquifers?

Abstract: In the method of deterministic geostatistics (sensu Issaks and Srivastava, 1988), highlyresolved data sets are used to compute sample spatial-bivariate statistics within a deterministic framework. The general goal is to observe what real, highly resolved, sample spatial-bivariate correlation looks like when it is well-quantified in naturally-occurring sedimentary aquifers.Furthermore, it is to understand how this correlation structure, (i.e. shape and correlation range) is related to independent and physically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 42 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…Reliable characterization of heterogeneous subsurface structures is crucial for earth sciences and other related applications such as groundwater management and contamination, geological carbon storage, radioactive waste disposal, and geothermal applications (Allen‐King et al., 2015; de Barros et al., 2013; de Barros, 2018; Dentz et al., 2020; Ershadnia et al., 2021; FernĂ ndez‐Garcia et al., 2005; Fiori et al., 2010; GĂłmez‐HernĂĄndez et al., 2017; Kitanidis, 2015; Ritzi & Soltanian, 2015; Sanchez‐Vila et al., 2006; M. R. Soltanian et al., 2015; Sudicky, 1986; Wallace et al., 2021; Weissmann et al., 2015). The poorly estimated subsurface structure may introduce a larger bias into dynamic responses prediction than inappropriate model parameters (Dai et al., 2020; FernĂ ndez‐Garcia et al., 2002, 2004, 2005; Harp et al., 2008; Pedretti et al., 2013; Riva et al., 2008; Sanchez‐Vila et al., 2010; Wallace & Soltanian, 2021; Ye et al., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Reliable characterization of heterogeneous subsurface structures is crucial for earth sciences and other related applications such as groundwater management and contamination, geological carbon storage, radioactive waste disposal, and geothermal applications (Allen‐King et al., 2015; de Barros et al., 2013; de Barros, 2018; Dentz et al., 2020; Ershadnia et al., 2021; FernĂ ndez‐Garcia et al., 2005; Fiori et al., 2010; GĂłmez‐HernĂĄndez et al., 2017; Kitanidis, 2015; Ritzi & Soltanian, 2015; Sanchez‐Vila et al., 2006; M. R. Soltanian et al., 2015; Sudicky, 1986; Wallace et al., 2021; Weissmann et al., 2015). The poorly estimated subsurface structure may introduce a larger bias into dynamic responses prediction than inappropriate model parameters (Dai et al., 2020; FernĂ ndez‐Garcia et al., 2002, 2004, 2005; Harp et al., 2008; Pedretti et al., 2013; Riva et al., 2008; Sanchez‐Vila et al., 2010; Wallace & Soltanian, 2021; Ye et al., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Using indicator geostatistics, several works have provided a more realistic link between sedimentary architecture data (e.g., mean length and volume proportions of facies types) at different scales and the time‐evolution of solute transport metrics (e.g., Dai et al., 2004; 2019, 2020; Ramanathan et al., 2010; Ritzi & Soltanian, 2015; Soltanian, Ritzi, Dai, et al., 2015a; Soltanian et al., 2020). The most important insight from these studies is that the spatial‐bivariate correlation structure of K is directly defined by the transition probability structure (i.e., probability of transitioning from one facies type to another), with the main contributions from cross‐transition probability.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate representation of solute transport processes (e.g., dispersion, mixing, and dilution) is important for various porous media‐related applications such as hydrogeology, soil physics, environmental engineering and sciences, water resources management, and petroleum engineering (de Barros et al., 2015; Ershadnia, Hajirezaie, et al., 2021; Ershadnia, Wallace, et al., 2021; Fiori & Dagan, 2000; Fiori, 2001; Jha et al., 2011; JimĂ©nez‐MartĂ­nez et al., 2015; Kitanidis and McCarty, 2012). Large‐scale field experiments (e.g., Borden, MADE, Cape Cod) have revealed that spatial heterogeneity in physical and geochemical sediment properties, as well as local‐scale dispersion, are among the primary underlying mechanisms which govern solute transport processes (Anderson & McCray, 2011; Attinger et al., 2004; Bianchi et al., 2011; Dai et al., 2004; Fiori & Dagan, 1999; Freyberg, 1986; Gelhar, 1986; Ritzi & Soltanian, 2015; Salamon et al., 2007; Sudicky & Illman, 2011; Zheng et al., 2011). Heterogeneous aquifer hydraulic conductivity ( K ) results in erratic solute distributions, which increase solute surface area and enhance spreading and mixing (Burr et al., 1994; de Barros et al., 2015; Dentz et al., 2011, 2018; Kitanidis, 1994; Sanchez‐Vila et al., 2006; Werth et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The structure estimated by sparse geological data typically involves great uncertainty (J. Chen & Rubin, 2003). This uncertainty may introduce significant biases in numerical simulations of flow and solute transport (Carrera, 1993; Carrera et al., 2005; Dai et al., 2014; Dai et al., 2020; Dentz et al., 2020; Geng et al., 2020; Nowak et al., 2010; Rajaram & Gelhar, 1995; Ritzi & Soltanian, 2015; Soltanian et al., 2019; Vrugt et al., 2005). Therefore, how to effectively use sparse observations, direct or indirect, to obtain a more realistic view of subsurface sedimentary structures in practice is an essential issue (Doherty, 2003; Keating et al., 2010).…”
Section: Introductionmentioning
confidence: 99%